An Implementation Of Environmental Law In Medan City Related To Waste Management System - Mochammad Erwin Radityo (Jurnal Ekonomi, 2024)
This study examines the implementation of environmental law in Medan City in relation to waste management. Medan, as one of the largest cities in Indonesia, faces significant challenges in managing waste due to rapid population growth and urbaniza-tion. The purpose of this study is to analysed the effectiveness of environmental law reg-ulations governing waste management in Medan and to identify factors that support and hinder the implementation of these policies. The research employs a qualitative ap-proach, collecting data through interviews, observations, and document reviews related to waste management policies. The findings reveal that although regulations exist to govern waste management in Medan, their implementation faces various obstacles, in-cluding low public awareness, limited waste management facilities, and insufficient law enforcement by authorities. The study concludes that collaboration among the govern-ment, community, and private sector is crucial to optimizing sustainable waste manage-ment. Increased public awareness about environmental regulations and the provision of adequate infrastructure are essential to ensure that waste management is effective and environmentally friendly.